Free Radical scavenging effect of Adenum Obesium in Streptozotocin Challenged Diabetic Rats. - SIREESHA KALVA; RAGHUNANDAN. N (International Journal of Pharma and Bio Sciences, 2017)
The present study was aimed to investigate the invitro and invivo antioxidant activities of two extracts i.e, methanolic extract and ethylacetate extract of Adenium obesum (MEAO,EAEAO)flowers which belong to family apocyanacea. The antioxidant activities of the two extracts had been evaluated by using standard invitro and invivo models in streptozotocin induced diabetic rats. The invitro antioxidant studies were determined by the percentage inhibition values estimated for DPPH(2,2-diphenyl-1-picrylhydrazyl) and Nitric oxide assays.The invivo antioxidant study was determined by evaluating enzymatic antioxidants such as Superoxide dismutase (SOD), Lipidperoxidase(LPO) and Catalase(CAT) in hepatic tissues of STZ induced diabetic rats.The results showed a significant percent inhibition in DPPH and NO assay when compared to diabetic control group.Ascorbic acid is taken as a standard antioxidant. The drug treated groups has shown an increase in the SOD, CAT and decreased Melondialdehyde levels as well significantly. Based on this study it was concluded that the methanolic and ethylacetate extracts of dried flowers of adenium obesum showed potent invivo and invitro antioxidant activity in streptozotocin challenged diabetic rat models.